Presiding Judge Mario Olmos Keynotes Fresno County Bar Association Luncheon re Court Filings - Watkins, Howard::::::::: (1989)
Fresno Superior Court Judge Mario Olmos discussing significant increases in criminal and civil filings and need for more Pro Tem Judges